ISLAMIC POLITICAL COMMUNICATION ETHICS AND GENDER JUSTICE: AN ANALYSIS OF THE PRINCIPLE OF AL-MUSAWAH IN THE REVISION OF THE ELECTION - M. Taufiq Hidayah Tanjung; Iskandar Zulkarnain; Mailin Mailin; Wani Oktafia (Pusat Studi Gender dan Anak, 2025)
This study aims to analyze gender-based political communication and the fulfillment of women’s rights from the perspective of political philosophy and ethics, particularly in the context of revising Indonesia’s Election Law. The main focus of this research is to understand how women’s social positions, lived experiences, experiential knowledge, and power relations influence political communication processes and public policy formulation within a democratic system. This research employs a qualitative library research method by examining books, academic journals, laws and regulations, and scholarly works relevant to gender issues, political communication, democracy, and political ethics. The findings indicate that gender-based political communication is a crucial normative and ethical instrument for realizing substantive, just, and inclusive democracy. Based on Standpoint Theory analysis, women, as a structurally less dominant group, possess unique perspectives derived from their social and political experiences; however, these perspectives are often marginalized in legislative and decision-making processes. This study emphasizes that affirmative policies, such as women’s representation quotas in the revision of the Election Law, are not merely legal-formal mechanisms but also represent moral recognition of women’s lived experiences and corrective efforts to address power imbalances, thereby contributing to the strengthening of justice principles, gender equality, and respect for human rights in Indonesian democracy.